Insulating film

JP2025034179APending Publication Date: 2025-03-13POLYPLASTICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023140404
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0008】 本開示によれば、靭性に優れかつ低誘電正接である絶縁フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034179000001_ABST
    Figure 2025034179000001_ABST
Patent Text Reader

Abstract

To provide an insulating film with superior toughness and low dielectric loss tangent.SOLUTION: An insulating film comprises an all-aromatic polyester comprising, as essential structural components, the following structural units I, II, III, and IV. In the structural unit III, Ar1 represents 2,6-naphthalene or 4,4'-biphenylene. Based on the total structural units, the content of I is 15-30 mol%, the content of II is 20-35 mol%, the content of III is 15-30 mol%, and the content of IV is 20-35 mol%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to insulating films. [Background technology]

[0002] A printed wiring board used in electronic devices such as communication devices and information processing devices is composed of a laminate having a substrate made of an insulating material and a circuit pattern layer made of a conductive material on the substrate. In order to meet the demand for smaller and thinner compact communication devices such as mobile phones, attempts have been made to form the substrate from a resin film to produce a flexible printed wiring board.

[0003] On the other hand, liquid crystalline resins such as wholly aromatic polyesters are widely used in various fields as high-performance engineering plastics because they have a good balance of excellent fluidity, mechanical strength, heat resistance, chemical resistance, electrical properties, etc. Most of the wholly aromatic polyesters currently on the market contain aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid as a main component (e.g., Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-79754 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, because the molecular chains of fully aromatic polyesters tend to be oriented, when they are molded into a film, the strength in the oriented direction is reduced, and the film may break. In addition, in the next-generation mobile communication systems that use high-frequency radio waves, insulating films with lower dielectric tangents are required to reduce transmission loss.

[0006] An object of the present disclosure is to provide an insulating film that has excellent toughness and a low dielectric tangent. [Means for solving the problem]

[0007] The present disclosure includes the following aspects. [1] (A) An insulating film containing a wholly aromatic polyester, The (A) wholly aromatic polyester contains, as essential components, the following structural units (I), (II), (III) and (IV): Contains JPEG2025034179000002.jpg67170, Ar1 in the structural unit (III) represents 2,6-naphthalene or 4,4'-biphenylene; The content of the structural unit (I) is 15 to 30 mol % based on all structural units, The content of the structural unit (II) is 20 to 35 mol % based on all structural units, The content of the structural unit (III) is 15 to 30 mol % based on all structural units, An insulating film, wherein the content of the structural unit (IV) is 20 to 35 mol % based on all structural units. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide an insulating film that has excellent toughness and a low dielectric tangent. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of an insulating film according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a printed wiring board including an insulating film according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a printed wiring board including an insulating film according to an embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view of a printed wiring board including an insulating film according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made within the scope of the present disclosure. Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. In addition, when multiple upper and lower limit values ​​are described for a specific parameter, any upper and lower limit values ​​among these upper and lower limit values ​​can be combined to form a suitable numerical range. In addition, the lower and / or upper limit values ​​of the numerical range described in this disclosure are numerical values ​​within the numerical range and may be replaced with numerical values ​​shown in the examples. The expression "X to Y" indicating a numerical range means "X or more and Y or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments.

[0011] [Insulating film] The insulating film according to the present embodiment contains (A) a wholly aromatic polyester, The (A) wholly aromatic polyester contains, as essential components, the following structural units (I), (II), (III) and (IV): Contains JPEG2025034179000003.jpg67170, Ar1 in the structural unit (III) represents 2,6-naphthalene or 4,4'-biphenylene; The content of the structural unit (I) is 15 to 30 mol % based on all structural units, The content of the structural unit (II) is 20 to 35 mol % based on all structural units, The content of the structural unit (III) is 15 to 30 mol % based on all structural units, The content of the structural unit (IV) is 20 to 35 mol % based on all structural units.

[0012] The insulating film described above has excellent toughness and can achieve a low dielectric loss tangent. The reason for this is not clear at this stage, but a non-limiting mechanism is thought to be that the (A) wholly aromatic polyester does not contain a structural unit derived from an aromatic hydroxycarboxylic acid as a main component, and contains the structural units (I) to (IV) in a predetermined amount, thereby preventing the dielectric loss tangent from increasing at high frequencies (e.g., 15 GHz), and also improves toughness to the extent that the orientation of the molecular chains is suppressed and the film is less likely to break even when formed into a film. In this specification, the "main component" means a component that is contained in 50 mol % or more of all structural units. In Patent Document 1, a film composed of a liquid crystal polymer containing a structural unit derived from an aromatic hydroxycarboxylic acid as a main component is studied, and a low dielectric loss tangent is achieved by increasing the content of structural units derived from 6-hydroxy-2-naphthoic acid (hereinafter sometimes referred to as "HNA"). In contrast, it was thought that it would be difficult to achieve a low dielectric loss tangent for (A) wholly aromatic polyesters that do not contain aromatic hydroxycarboxylic acids as a main component, since they do not contain structural units derived from HNA. However, by containing the structural units (I) to (IV) in predetermined amounts, it is possible to achieve excellent toughness and a low dielectric loss tangent.

[0013] In the present disclosure, the term "insulating film" refers to a film used for the purpose of electrical insulation. Details of insulating films will be described later.

[0014] In the present disclosure, the proportion (mol%) of each of the constituent units of the wholly aromatic polyester (A) can also be calculated from the monomer charge ratio when polymerizing the wholly aromatic polyester (A). Alternatively, the proportion (mol%) of each of the constituent units of the wholly aromatic polyester (A) can also be calculated by the pyrolysis gas chromatography method described in Polymer Degradation and Stability vol.76 (2002), 85-94.

[0015] <(A) Wholly aromatic polyester> The insulating film contains (A) a wholly aromatic polyester. (A) Wholly aromatic polyester contains the following structural units (I), (II), (III) and (IV) as essential components: Contains JPEG2025034179000004.jpg67170.

[0016] The structural unit (I) is derived from 1,4-phenylenedicarboxylic acid (hereinafter, sometimes referred to as "TA") and its polymerizable derivatives. Examples of the polymerizable derivatives include alkyl esters (the number of carbon atoms in the alkyl group is preferably about 1 to 4) and halides of 1,4-phenylenedicarboxylic acid. In the present embodiment, the wholly aromatic polyester (A) contains 15 to 30 mol% of the structural unit (I) based on all structural units. When the content of the structural unit (I) is 15 to 30 mol%, the toughness of the insulating film is easily increased and a low dielectric loss tangent is easily achieved. From the viewpoint of more easily achieving both the toughness and low dielectric loss tangent of the insulating film, the content of the structural unit (I) is preferably 15 to 28.75 mol%, more preferably 15 to 27.5 mol%, based on all structural units. The content of the structural unit (I) may be 15 mol%, 20 mol%, 25 mol%, or 27.5 mol% relative to all structural units, or may be within a range with these upper and lower limits. In one embodiment, the content of the structural unit (I) may be 17.5 to 26 mol% relative to all structural units.

[0017] The structural unit (II) is derived from 2,6-naphthalenedicarboxylic acid (hereinafter, sometimes referred to as "NDA") and its polymerizable derivatives. Examples of the polymerizable derivatives include alkyl esters (the number of carbon atoms in the alkyl group is preferably about 1 to 4) and halides of 2,6-naphthalenedicarboxylic acid. In the present embodiment, the wholly aromatic polyester (A) contains 20 to 35 mol% of the structural unit (II) relative to all structural units. When the content of the structural unit (II) is 20 to 35 mol%, the toughness of the insulating film is easily increased and a low dielectric loss tangent is easily achieved. From the viewpoint of more easily achieving both the toughness and low dielectric loss tangent of the insulating film, the content of the structural unit (II) is preferably 21.25 to 35 mol%, more preferably 22.5 to 35 mol%, relative to all structural units. The content of the structural unit (II) may be 22.5 mol%, 25 mol%, 30 mol%, or 35 mol% relative to all structural units, or may be within a range with these upper or lower limits. In one embodiment, the content of the structural unit (II) may be 24 to 32.5 mol% relative to all structural units.

[0018] In the structural unit (III), Ar1 represents 2,6-dihydroxynaphthalene (hereinafter, sometimes referred to as "NDO") or 4,4'-dihydroxybiphenyl (hereinafter, sometimes referred to as "BP"). That is, the structural unit (III) may be a unit derived from NDO and a polymerizable derivative thereof, or may be a unit derived from BP and a polymerizable derivative thereof, or may contain two or more of these. Examples of the polymerizable derivative of NDO include alkyl esters (the alkyl group preferably has about 1 to 4 carbon atoms) and halides of 2,6-dihydroxynaphthalene. Examples of the polymerizable derivative of BP include alkyl esters (the alkyl group preferably has about 1 to 4 carbon atoms) and halides of 4,4'-dihydroxybiphenyl.

[0019] In one embodiment, from the viewpoints of cost and availability, it is preferable that the structural unit (III) contains a unit derived from BP.

[0020] In this embodiment, the (A) wholly aromatic polyester contains 15 to 30 mol% of the structural unit (III) based on all structural units. When the content of the structural unit (III) is 15 to 30 mol%, the toughness of the insulating film is easily increased and a low dielectric loss tangent is easily realized. From the viewpoint of more easily achieving both the toughness and the low dielectric loss tangent of the insulating film, the content of the structural unit (III) is preferably 15 to 28.75 mol%, more preferably 15 to 27.5 mol%, based on all structural units. The content of the structural unit (III) may be 15 mol%, 20 mol%, or 25 mol%, based on all structural units, or may be within a range with these as the upper or lower limit. In one embodiment, the content of the structural unit (III) may be 17.5 to 26 mol% based on all structural units.

[0021] The structural unit (IV) is derived from 1,4-dihydroxybenzene (hereinafter sometimes referred to as "HQ") and its polymerizable derivatives. Examples of the polymerizable derivatives include alkyl esters (the alkyl group preferably has about 1 to 4 carbon atoms) and halides of 1,4-dihydroxybenzene. In this embodiment, the (A) wholly aromatic polyester contains 20 to 35 mol% of the structural unit (IV) relative to all structural units. When the content of the structural unit (IV) is 20 to 35 mol%, the toughness of the insulating film is easily increased and a low dielectric loss tangent is easily realized. From the viewpoint of more easily achieving both the toughness and the low dielectric loss tangent of the insulating film, the content of the structural unit (IV) is preferably 21.25 to 35 mol%, more preferably 22.5 to 35 mol%, relative to all structural units. The content of the structural unit (IV) may be 25 mol%, 30 mol%, or 35 mol%, relative to all structural units, or may be within a range with these as the upper or lower limit. In one embodiment, the content of the structural unit (IV) may be 24 to 32.5 mol% relative to all structural units.

[0022] From the viewpoint of easily obtaining an insulating film having higher toughness and a low dielectric loss tangent, the compounding ratio (molar ratio) of the structural units (I) and (II) derived from an aromatic dicarboxylic acid is preferably 0.7 to 2.4, more preferably 0.8 to 2.3, as (II) / (I). In one embodiment, the compounding ratio (molar ratio) of the structural units (I) and (II) may be 1.0 to 2.3, or 1.0 to 1.5, as (II) / (I).

[0023] From the viewpoint of easily obtaining an insulating film having higher toughness and a low dielectric tangent, the compounding ratio (molar ratio) of the structural units (III) and (IV) derived from an aromatic diol is preferably 0.9 to 2.4, more preferably 1.0 to 2.3, and even more preferably 1.0 to 1.5, as (IV) / (III).

[0024] From the viewpoint of obtaining an insulating film having higher toughness and a low dielectric loss tangent, the ratio (molar ratio) of the total amount of the structural units (I) and (II) to the total amount of the structural units (III) and (IV) is preferably 0.3 to 1.6, more preferably 0.4 to 1.6, even more preferably 0.7 to 1.5, and particularly preferably 0.8 to 1.5, or may be 0.9 to 1.5, 1.0 to 1.5, or may be 1.0 to 1.3, as [(I)+(II)] / [(III)+(IV)]. In one embodiment, the total amount of the structural units (I) and (II) and the total amount of the structural units (III) and (IV) may be equal.

[0025] In one embodiment, the total content of the structural units (I) to (IV) in the wholly aromatic polyester (A) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, based on all the structural units of the wholly aromatic polyester (A). From the viewpoint of making it easier to obtain an insulating film with higher toughness and a low dielectric tangent, the wholly aromatic polyester (A) may contain only the structural units (I) to (IV) (i.e., the total content of the structural units (I) to (IV) may be 100 mol % based on all the structural units).

[0026] The (A) wholly aromatic polyester may contain other structural units in addition to the above-mentioned structural units (I) to (IV). Examples of the other structural units include the following structural unit (V): JPEG2025034179000005.jpg20170 and its constituent units, (VI): Examples include JPEG2025034179000006.jpg18170.

[0027] The structural unit (V) is derived from 1,3-phenylenedicarboxylic acid (common name: isophthalic acid) and its polymerizable derivatives. Examples of the polymerizable derivatives include alkyl esters (the alkyl group preferably has about 1 to 4 carbon atoms) and halides of 1,3-phenylenedicarboxylic acid. From the viewpoint of making it easier to obtain an insulating film with higher toughness and a low dielectric loss tangent, the content of the structural unit (V) is preferably 0 to 5 mol % or less, and more preferably 0 to 2.5 mol % or less, based on the total structural units. In one aspect, from the viewpoint of making it easier to obtain an insulating film with higher toughness and a low dielectric loss tangent, the (A) wholly aromatic polyester may be configured so as not to contain the structural unit (V).

[0028] The structural unit (VI) is derived from 1,3-dihydroxybenzene (common name: resorcinol) and its polymerizable derivatives. Examples of the polymerizable derivatives include alkyl esters (the alkyl group preferably has about 1 to 4 carbon atoms) and halides of 1,3-dihydroxybenzene. The content of the structural unit (VI) is preferably 0 to 5 mol % or less, and more preferably 0 to 2.5 mol % or less, based on the total structural units. In one aspect, from the viewpoint of making it easier to obtain an insulating film with higher toughness and a low dielectric loss tangent, (A) wholly aromatic polyester may be configured so as not to contain the structural unit (VI).

[0029] (A) The wholly aromatic polyester preferably does not contain a structural unit derived from an aromatic hydroxycarboxylic acid (e.g., p-hydroxybenzoic acid (hereinafter sometimes referred to as "HBA"), 6-hydroxy-2-naphthoic acid (hereinafter sometimes referred to as "HNA"), etc.). When no structural unit derived from an aromatic hydroxycarboxylic acid is contained, an insulating film with higher toughness and a lower dielectric loss tangent is more easily obtained.

[0030] In one embodiment, the wholly aromatic polyester (A) is preferably a liquid crystalline resin that exhibits optical anisotropy when melted. When the wholly aromatic polyester (A) is a liquid crystalline resin, it becomes easier to obtain an insulating film that has both toughness and a low dielectric tangent. The fact that the resin exhibits optical anisotropy when melted can be confirmed by a conventional polarization inspection method using crossed polarizers. More specifically, the optical anisotropy of (A) wholly aromatic polyester can be confirmed by using a polarizing microscope (e.g., Olympus Corporation, product name: BX51) to melt a sample placed on a hot stage (e.g., Linkam Corporation, product name: CSS450) and observing the sample at a magnification of 150 times under a nitrogen atmosphere. Liquid crystal resins are optically anisotropic and transmit light when inserted between crossed polarizers. If the sample is optically anisotropic, polarized light will transmit even when the sample is in a molten, stationary liquid state, for example.

[0031] Nematic liquid crystal resins undergo a marked decrease in viscosity at temperatures above their melting point, and therefore, in general, the ability to exhibit liquid crystallinity at or above the melting point is an indicator of processability.

[0032] In one embodiment, the melt viscosity of the (A) wholly aromatic polyester at a temperature 10 to 40°C higher than the melting point of the (A) wholly aromatic polyester and at a shear rate of 1000 / sec is preferably 1000 Pa·s or less, more preferably 4 to 500 Pa·s, even more preferably 4 to 250 Pa·s, and particularly preferably 5 to 100 Pa·s. When the (A) wholly aromatic polyester has a melt viscosity within the above range, the film formability of the insulating film according to this embodiment is improved. In the present disclosure, the melt viscosity refers to the melt viscosity measured in accordance with ISO11443.

[0033] The (A) wholly aromatic polyester may be a blend of two or more kinds of wholly aromatic polyesters differing in the contents of the structural units (I) to (IV), the contents of the structural units (V) and (IV) which may be contained as necessary, the melt viscosity, etc. When two or more kinds of wholly aromatic polyesters are blended, the amounts of the structural units (I) to (IV) in the (A) wholly aromatic polyester after blending can be adjusted so that they fall within the above-mentioned ranges.

[0034] The content of the (A) wholly aromatic polyester in the insulating film according to this embodiment is preferably 80 to 100 mass % relative to the total mass of the insulating film, and more preferably 90 to 100 mass %. When the content of the (A) wholly aromatic polyester in the insulating film is within the above range, the inherent heat resistance, chemical resistance, electrical properties, etc. of the wholly aromatic polyester can be easily exhibited. In one embodiment, the content of the (A) wholly aromatic polyester in the insulating film can be 98 mass % or more, 99 mass % or more, or 100 mass % relative to the total mass of the insulating film.

[0035] The content of the (A) wholly aromatic polyester in the resin components contained in the insulating film according to this embodiment is preferably 80 mass % or more of the total resin components, more preferably 90 mass % or more, and even more preferably 95 mass % or more, and can be 100 mass %.

[0036] The (A) wholly aromatic polyester has a flow initiation temperature of preferably 310° C. or less, more preferably 300° C. or less, and even more preferably 295° C. or less. By setting the flow initiation temperature to 310° C. or less, the (A) wholly aromatic polyester can have liquid crystallinity and excellent film formability at low temperatures. In one embodiment, the wholly aromatic polyester may have a flow initiation temperature of 292° C. or less. In one embodiment, the wholly aromatic polyester may have a flow initiation temperature of 290° C. or less or 280° C. or less.

[0037] The flow initiation temperature is the temperature at which the wholly aromatic polyester becomes fluid when heated by an external force, and can be measured by the following method. That is, the flow initiation temperature is measured using a capillary rheometer (e.g., a Flow Tester CFT-500 model manufactured by Shimadzu Corporation) as the temperature (°C) at which the melt viscosity is 48,000 poise when a sample resin heated and melted at a heating rate of 4°C / min is extruded under a load of 100 kg / cm2 from a nozzle with an inner diameter of 1 mm and a length of 10 mm.

[0038] The method for producing the wholly aromatic polyester (A) is not particularly limited, and the polyester can be produced by a known method such as direct polymerization or transesterification from the above-mentioned monomer compound (or a mixture of monomers). Generally, however, a melt polymerization method, a solution polymerization method, a slurry polymerization method, a solid-phase polymerization method, or a combination of two or more of these methods is used, and the melt polymerization method or a combination of the melt polymerization method and the solid-phase polymerization method is preferably used.

[0039] In the case of a compound capable of forming an ester, it may be used in the polymerization in its original form, or may be used after being modified from a precursor to a derivative capable of forming an ester using an acylating agent or the like in a step prior to the polymerization. Examples of the acylating agent include carboxylic anhydrides such as acetic anhydride.

[0040] The wholly aromatic polyester (A) produced by the above reaction can be further subjected to solid-phase polymerization by heating in an inert gas under normal pressure or reduced pressure to increase the molecular weight. The solid-phase polymerization can be carried out by a conventional method. For example, the solid-phase polymerization can be carried out by heating the raw material resin (the wholly aromatic polyester obtained by the polycondensation reaction) at a temperature 10 to 120°C lower than the liquid crystal formation temperature of the raw material resin (the wholly aromatic polyester obtained by the polycondensation reaction) in an inert gas flow such as nitrogen gas under reduced pressure or vacuum. Since the melting point of the wholly aromatic polyester increases as the solid-phase polymerization proceeds, it is also possible to carry out the solid-phase polymerization at a temperature equal to or higher than the original melting point of the raw material resin. The solid-phase polymerization can be carried out at a constant temperature or can be increased stepwise. The heating method is not particularly limited, and microwave heating, heater heating, etc. can be used.

[0041] A known catalyst can be used in each of the above reactions. Representative examples include metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, antimony trioxide, and tris(2,4-pentanedionato)cobalt(III), and organic compound catalysts such as 1-methylimidazole and 4-dimethylaminopyridine. The catalyst preferably contains at least one selected from these. The same catalyst may be used in the acylation reaction and the polycondensation reaction (solid-phase polymerization reaction, if necessary). The amount of the catalyst used is generally about 0.001 to 1 mass% relative to the total weight of the monomer, and is particularly preferably about 0.01 to 0.2 mass%.

[0042] In each of the above reactions, all the raw material monomers, fatty acid anhydride and catalyst can be charged into the same reaction vessel to initiate the reaction (single-stage system), or the aromatic diol component can be acylated with the fatty acid anhydride and then reacted separately with the aromatic dicarboxylic acid component (two-stage system).

[0043] <(B) Filler> The insulating film may contain an organic or inorganic filler as the filler (B) as required. Examples of the organic or inorganic filler include one or more selected from the group consisting of talc, mica, silica, glass flakes, graphite, wollastonite, glass beads, glass balloons, calcium carbonate, magnesium carbonate, titanium oxide, glass fiber, silica alumina fiber, alumina fiber, carbon fiber, potassium titanate fiber, aluminum borate fiber, and aramid fiber. Among these, it is preferable to contain one or more selected from talc, mica, silica, wollastonite, and potassium titanate fiber from the viewpoint of excellent balance between physical properties and cost. When using the above filler, a sizing agent or a surface treatment agent can be used as required.

[0044] From the viewpoint of improving film formability, the content of the (B) filler is preferably 0 to 20 parts by mass, more preferably 0 to 10 parts by mass, and even more preferably 0 to 5 parts by mass, relative to 100 parts by mass of the (A) wholly aromatic polyester. In one embodiment, the insulating film may not contain an organic or inorganic filler.

[0045] <(C) Elastomer> The insulating film may contain an elastomer (C) as required. Examples of the elastomer (C) include an epoxy group-containing olefin polymer and an epoxy group-containing styrene polymer.

[0046] From the viewpoint of improving film-forming properties and toughness, the content of the (C) elastomer is preferably 0 to 20 parts by mass, more preferably 0 to 10 parts by mass, and even more preferably 0 to 5 parts by mass, relative to 100 parts by mass of the (A) wholly aromatic polyester. In one embodiment, since the insulating film has excellent toughness, the content of the (C) elastomer may be 2.5 mass % or less based on the total mass of the insulating film, or the insulating film may not contain the (C) elastomer.

[0047] <Other ingredients> The insulating film may further contain other components such as a nucleating agent, a pigment such as carbon black or an inorganic calcined pigment, an antioxidant, a stabilizer, a plasticizer, a lubricant, a release agent, a flame retardant, etc. These other components may be used alone or in combination of two or more. When the insulating film contains other components, it is preferable that the content of the other components is within the range of 5 mass % or less based on the total mass of the insulating film.

[0048] <Insulating film> (Physical Properties) Fig. 1 shows a schematic cross-sectional view of an insulating film 1 according to this embodiment. The insulating film 1 in Fig. 1 is composed of a single layer, but may be composed of two or more laminated layers each containing the wholly aromatic polyester (A) and each containing the structural units (I) to (IV) within the above-mentioned range. When the insulating film is composed of two or more laminated layers, the contents of the structural units (I) to (IV) in the wholly aromatic polyester (A) contained in each layer may be the same or different within the above-mentioned range.

[0049] The thickness of the insulating film is not limited, and for example, when the insulating film is used for a printed wiring board, it is preferably 1 to 1000 μm, more preferably 5 to 500 μm, and further preferably 10 to 300 μm. When the insulating film is composed of two or more layers, the total thickness of the insulating film can be adjusted to the above range. In this specification, the thickness of a film or layer is defined as the arithmetic average value measured at any five points on the insulating film using a micrometer.

[0050] The insulating film preferably has a dielectric loss tangent of 0.001 or less at a measurement frequency of 15 GHz, as measured by the split post dielectric resonator method (SPDR method). If the dielectric loss tangent is 0.001 or less at a measurement frequency of 15 GHz, a low dielectric loss tangent can be achieved even in high frequency bands, and transmission loss can be reduced even when the insulating film is used in a printed wiring board for communication devices.

[0051] The insulating film preferably has a relative dielectric constant of 3.5 or less, more preferably 3.3 or less, at a measurement frequency of 15 GHz, as measured by the SPDR method. If the relative dielectric constant is 3.5 or less at a measurement frequency of 15 GHz, an excellent signal transmission speed can be easily achieved even when the insulating film is used in a printed wiring board of a communication device.

[0052] The insulating film has a bending strain of preferably 10.0% or more, more preferably 10.1% or more, even more preferably 10.3% or more, even more preferably 10.9% or more, and particularly preferably 11.0% or more, measured on a 300 μm thick test piece in accordance with ASTM D790. If the bending strain is 10.0% or more, the insulating film can have better toughness, and can be prevented from breaking even when the insulating film is made thinner (for example, 300 μm or less).

[0053] (Manufacturing method) The insulating film can be obtained by molding (A) wholly aromatic polyester or a composition containing (A) wholly aromatic polyester by a known molding method such as extrusion molding, press molding, or injection molding. Examples of the extrusion molding method include the well-known T-die method, lamination stretching method, inflation method, etc. Examples of the press molding method include the well-known hot press method, stamping molding, etc. Examples of the injection molding method include a method in which a molten resin is injected into a cavity of a mold using a well-known injection molding machine. In order to control the orientation of molecular chains, the insulating film may be stretched in the mechanical axis direction (MD) and / or the direction perpendicular thereto (TD) during molding or after cooling. The stretching may be performed by any of the known biaxial stretching and uniaxial stretching, but biaxial stretching is preferred because it is easier to control the degree of molecular orientation.

[0054] (Application) The insulating film according to the present embodiment has the characteristics of excellent toughness and low dielectric tangent, and therefore can be suitably used as an insulating material for electronic devices, for example, as a printed wiring board material. The insulating film according to the present embodiment can be folded or rolled into a cylindrical shape, so it can also be used as an insulating film for flexible printed wiring boards. The insulating film according to the present embodiment can be used to manufacture a printed wiring board (preferably a flexible printed wiring board). That is, the insulating film according to one embodiment can be used for a printed wiring board (preferably for a flexible printed wiring board). Specific examples of printed wiring board materials include an insulating substrate for a printed wiring board, a bonding sheet for bonding substrates having a conductor circuit (circuit pattern) formed on the substrate surface, and a coverlay formed on the surface of a circuit pattern layer.

[0055] The insulating film according to this embodiment can also be used as a laminate with a metal or a resin. Examples of metals include copper, gold, silver, nickel, and aluminum, among which copper is preferred. The metal is preferably used as a metal foil to form a laminate, and copper foil is particularly preferred. The thickness of the layer containing the metal is not limited, and can be, for example, 1 to 1000 μm. Examples of the resin include polyolefins such as polypropylene and polyethylene, liquid crystal polymers other than (A) wholly aromatic polyesters, amorphous polyarylates, polycarbonates, polyamides, other polyesters, polyacetals, polyphenylene ethers, polysulfones, polyethersulfones, polyetherimides, polyetheretherketones, polyamideimides, fluororesins such as polytetrafluoroethylene, phenolic resins, epoxy resins, and polyimide resins. A laminated film may be formed by laminating a resin film containing one or more selected from these with the insulating film according to the present embodiment. Among these, a laminate with a resin film selected from the group consisting of (A) liquid crystal polymer films other than wholly aromatic polyesters, polyimide films, polytetrafluoroethylene films, and polyetheretherketones is preferred, a laminate with (A) liquid crystal polymer films or polyimide films other than wholly aromatic polyesters is more preferred, and a laminate with (A) liquid crystal polymer films other than wholly aromatic polyesters is even more preferred. The thickness of the resin film laminated with the insulating film is not limited, and may be, for example, 1 to 1000 μm.

[0056] [Printed wiring board] The printed wiring board according to the present embodiment includes the insulating film and a circuit pattern layer. FIG. 2 shows a schematic cross-sectional view of a printed wiring board 10 according to one embodiment. The printed wiring board 10 in FIG. 2 includes the insulating film 1 and a circuit pattern layer 2 formed on one surface of the insulating film 1. In this case, the insulating film 1 can function as an insulating base material. The circuit pattern layer 2 is formed of a conductive material, and a circuit pattern having an arbitrary shape is formed on the circuit pattern layer 2. Examples of the conductive material include metals such as copper, gold, silver, nickel, and aluminum. In the printed wiring board 10 shown in FIG. 2, the circuit pattern layer 2 is formed only on one surface of the insulating film 1, but the circuit pattern layer 2 may be formed on both surfaces of the insulating film 1. Fig. 3 shows a schematic cross-sectional view of a printed wiring board 10 according to another embodiment. The printed wiring board 10 in Fig. 3 has a configuration in which substrates 3, each having a circuit pattern layer 2 formed on the surface thereof, are bonded together by the insulating film 1 described above. In this case, the insulating film 1 can function as a bonding sheet. The material of the substrate 3 is not limited, and examples thereof include a substrate containing a resin different from that of the insulating film 1 (e.g., epoxy resin, polyimide, fluororesin, etc.). Fig. 4 shows a schematic cross-sectional view of a printed wiring board 10 according to still another embodiment. In Fig. 4, the printed wiring board 10 has a configuration in which the above-mentioned insulating film 1 is provided on the surface of a circuit pattern layer 2 formed on a substrate 3. In this case, the insulating film 1 can act as a coverlay for the circuit pattern layer 2.

[0057] Electronic components such as resistors, ICs, capacitors, etc. (not shown) can be attached to the printed wiring board by soldering or the like.

[0058] The printed wiring board according to this embodiment can achieve a low dielectric tangent even in a high frequency band (for example, 15 GHz). The applications of the printed wiring board are not limited, and the printed wiring board may be mounted, for example, on network devices, communication devices such as mobile phones, servers, AI processors, in-vehicle and aircraft devices, and home game consoles.

[0059] The method for producing the printed wiring board is not limited, and the printed wiring board can be obtained by a known method such as a subtractive method in which a metal foil is laminated to an insulating film and then etched, or an additive method in which a circuit pattern layer is directly formed on an insulating film by plating or the like.

[0060] A non-limiting list of exemplary embodiments and combinations of exemplary embodiments of the present disclosure are disclosed below. [1] (A) An insulating film containing a wholly aromatic polyester, The (A) wholly aromatic polyester contains, as essential components, the following structural units (I), (II), (III) and (IV): Contains JPEG2025034179000007.jpg67170, Ar1 in the structural unit (III) represents 2,6-naphthalene or 4,4'-biphenylene; The content of the structural unit (I) is 15 to 30 mol % based on all structural units, The content of the structural unit (II) is 20 to 35 mol % based on all structural units, The content of the structural unit (III) is 15 to 30 mol % based on all structural units, An insulating film, wherein the content of the structural unit (IV) is 20 to 35 mol % based on all structural units. [2] The insulating film according to [1], wherein the total content of the structural units (I) to (IV) is 90 to 100 mol % based on all structural units of the wholly aromatic polyester (A). [3] The insulating film according to [1] or [2], which has a dielectric loss tangent of 0.001 or less at a measurement frequency of 15 GHz as measured by a split post dielectric resonator method. [4] The insulating film according to any one of [1] to [3], which is for use in a printed wiring board. [5] Use of the insulating film according to any one of [1] to [4] for producing a printed wiring board. [6] A printed wiring board comprising the insulating film according to any one of [1] to [5] and a circuit pattern layer.

[0061] The configurations and combinations thereof in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate without departing from the spirit of the present disclosure. The present disclosure is not limited to the embodiments. Each feature disclosed herein may be combined with any other feature disclosed herein. EXAMPLES

[0062] The present disclosure will be described in more detail below by showing examples, but interpretation of the present disclosure is not limited to these examples.

[0063] [Synthesis Example 1] A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, fatty acid metal salt catalyst, and fatty acid anhydride, and nitrogen replacement was started. (I) 1,4-phenylenedicarboxylic acid (TA) 0.5 moles (25 mole%) (II) 2,6-naphthalenedicarboxylic acid (NDA) 0.5 moles (25 mole%) (III) 4,4'-dihydroxybiphenyl (BP) 0.5 mol (25 mol%) (IV) 1,4-dihydroxybenzene (HQ) 0.5 moles (25 mole percent) Potassium acetate catalyst 150ppm Acetic anhydride 2.08 mol (1.04 equivalents based on the total amount of hydroxyl groups of BP and HQ)

[0064] After the raw materials were charged, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 3 hours (acylation step). Then, the temperature was further raised to 360°C over 4.5 hours, and the pressure was reduced to 10 Torr (i.e., 1330 Pa) over 15 minutes, and polycondensation was carried out while distilling acetic acid, excess acetic anhydride, and other low boiling points (polycondensation reaction step). After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel. Then, the strands were pelletized to obtain fully aromatic polyester pellets.

[0065] [Synthesis Examples 2-7] Wholly aromatic polyester pellets were obtained in the same manner as in Synthesis Example 1, except that the raw material monomers and their blending amounts were as shown in Table 1.

[0066] [Synthesis Example 8] (Comparative Synthesis Example) A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, fatty acid metal salt catalyst, and fatty acid anhydride, and nitrogen replacement was started. (I) 1,4-phenylenedicarboxylic acid (TA) 0.46 moles (25 mole percent) (III) 4,4'-dihydroxybiphenyl (BP) 0.46 mol (25 mol%) 4-Hydroxybenzoic acid (HBA) 0.037 mol (2 mol%) 6-Hydroxy-2-naphthoic acid (HNA) 0.883 mol (48 mol%) Potassium acetate catalyst 150ppm Acetic anhydride 1.914 mol (1.04 equivalents based on the total amount of hydroxyl groups of BP, HBA and HNA)

[0067] After the raw materials were charged, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 3 hours (acylation step). Then, the temperature was further raised to 360°C over 4.5 hours, and the pressure was reduced to 10 Torr (i.e., 1330 Pa) over 15 minutes, and polycondensation was carried out while distilling acetic acid, excess acetic anhydride, and other low boiling points (polycondensation reaction step). After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel. Then, the strands were pelletized to obtain fully aromatic polyester pellets.

[0068] [Synthesis Example 9] (Comparative Synthesis Example) (I) 1,4-phenylenedicarboxylic acid (TA) 0.28 moles (14 mole %) (III) 4,4'-dihydroxybiphenyl (BP) 0.4 mol (20 mol%) 1,3-phenylenedicarboxylic acid (IA) 0.12 moles (6 mole%) 4-Hydroxybenzoic acid (HBA) 1.2 moles (60 mole%) Potassium acetate catalyst 150ppm Acetic anhydride 2.08 mol (1.04 equivalents based on the total amount of hydroxyl groups of BP and HBA)

[0069] After the raw materials were charged, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 3 hours (acylation step). Then, the temperature was further raised to 360°C over 4.5 hours, and the pressure was reduced to 10 Torr (i.e., 1330 Pa) over 15 minutes, and polycondensation was carried out while distilling acetic acid, excess acetic anhydride, and other low boiling points (polycondensation reaction step). After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel. Then, the strands were pelletized to obtain fully aromatic polyester pellets.

[0070] [Synthesis Example 10] (Comparative Synthesis Example) A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, fatty acid metal salt catalyst, and fatty acid anhydride, and nitrogen replacement was started. 4-Hydroxybenzoic acid (HBA) 1660 moles (73 mole%) 6-Hydroxy-2-naphthoic acid (HNA) 837 moles (27 mole%) Potassium acetate catalyst 150ppm Acetic anhydride 2.08 mol (1.04 equivalents based on the total amount of hydroxyl groups of HBA and HNA)

[0071] After the raw materials were charged, the temperature of the reaction system was raised to 140°C and reacted at 140°C for 1 hour (acylation step). Then, the temperature was further raised to 325°C over 3.5 hours, and the pressure was reduced to 5 Torr (i.e., 667 Pa) over 20 minutes, and polycondensation was carried out while distilling acetic acid, excess acetic anhydride, and other low boiling points (polycondensation reaction step). After the stirring torque reached a predetermined value, nitrogen was introduced to change from a reduced pressure state to a normal pressure state and then to a pressurized state, and the polymer was discharged from the bottom of the polymerization vessel. Then, the strands were pelletized to obtain fully aromatic polyester pellets.

[0072] (Liquid crystallinity) The wholly aromatic polyesters obtained in Synthesis Examples 1 to 10 were melted on a hot stage manufactured by Linkam Co., Ltd., and observed under a nitrogen atmosphere at a magnification of 150 times under crossed Nicols using a polarizing microscope manufactured by Olympus Corporation. Those in which an optically anisotropic molten phase was formed are indicated by "Y" in Table 1.

[0073] (Flow starting temperature) The wholly aromatic polyesters obtained in Synthesis Examples 1 to 10 were melted at a heating rate of 4°C / min using a capillary rheometer (Shimadzu Corporation, Flow Tester CFT-500), and the temperature at which the melt viscosity was 4800 Pa s (48,000 poise) was measured when the polyesters were extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm under a load of 9.8 MPa (100 kg / cm2). The results are shown in Table 1.

[0074] [Examples 1 to 7, Comparative Examples 1 to 3] The wholly aromatic polyesters obtained in Synthesis Examples 1 to 10 were each used as shown in Table 1 and molded under the following conditions to obtain an insulating film (I) (30 mm × 20 mm × 100 μm) for dielectric property evaluation and an insulating film (II) (50 mm × 4 mm × 300 μm) for bending test evaluation. <Conditions for preparing insulating film (I)> Molding machine: Heat press molding machine ("Mini Test Press-10" manufactured by Toyo Seiki Co., Ltd.) Press temperature: Examples 1 to 4: 350°C Examples 5 to 7: 370°C Comparative Example 1: 370℃ Comparative Example 2: 350°C Comparative Example 3: 300℃ Pressure: 3MPa <Conditions for preparing insulating film (II)> Molding machine: Injection molding machine (Sumitomo Heavy Industries, Ltd. "SE-100DU") Cylinder Temperature: Examples 1 to 4: 350°C Examples 5 to 7: 370°C Comparative Example 1: 370℃ Comparative Example 2: 350°C Comparative Example 3: 300℃ Mold temperature: 90℃ Injection speed: 33mm / sec Holding pressure: 50MPa

[0075] The insulating films (I) and (II) obtained using the wholly aromatic polyesters obtained in Synthesis Examples 1 to 7 were used as the insulating films of Examples 1 to 7, and the insulating films (I) and (II) obtained using the wholly aromatic polyesters obtained in Synthesis Examples 8 to 10 were used as the insulating films of Comparative Examples 1 to 3.

[0076] (Dielectric properties) Using insulating film (I) (30mm x 20mm x 100μm), the relative dielectric constant and dielectric loss tangent were measured at a measurement frequency of 15GHz using a split post dielectric resonator method (SPDR method: Split post dielectric resonators method) under standard environmental conditions (23±2℃) and relative humidity of 45-55% using a network analyzer and a split post dielectric resonator method dielectric property evaluation device (both manufactured by Keysight Technologies). The results are shown in Table 1.

[0077] (Bending test) Using the insulating film (II) (50 mm × 4 mm × 300 μm), the bending strain at the maximum bending stress was measured under the following test conditions. The results are shown in Table 1. [Test conditions] Test speed: 2.0mm / min Distance between fulcrums 4.8mm Indenter radius: 0.5 mm Support radius: 0.5mm Elastic modulus: secant method

[0078] [Table 1] [Industrial Applicability]

[0079] INDUSTRIAL APPLICABILITY The insulating film according to the present embodiment has the properties of excellent toughness and a low dielectric tangent, and therefore can be suitably used as an insulating material in electronic devices, and has industrial applicability. [Explanation of symbols]

[0080] 1. Insulating film 2 Circuit pattern layer 3 Base material 10 Printed wiring board

Claims

1. (A) An insulating film containing a wholly aromatic polyester, The wholly aromatic polyester (A) contains, as essential components, the following structural units (I), (II), (III), and (IV): Including, Ar in structural unit (III) 1 represents 2,6-naphthalene or 4,4'-biphenylene; The content of the structural unit (I) is 15 to 30 mol % based on all structural units, The content of the structural unit (II) is 20 to 35 mol % based on all structural units, The content of the structural unit (III) is 15 to 30 mol % based on all structural units, An insulating film, wherein the content of the structural unit (IV) is 20 to 35 mol % based on all structural units.

2. 2. The insulating film according to claim 1, wherein the total content of the structural units (I) to (IV) is 90 to 100 mol % based on all structural units of the wholly aromatic polyester (A).

3. 3. The insulating film according to claim 1, wherein the dielectric loss tangent at a measurement frequency of 15 GHz measured by a split post dielectric resonator method is 0.001 or less.

4. The insulating film according to claim 1 or 2, which is for use in a printed wiring board.

5. 3. Use of the insulating film according to claim 1 or 2 for producing a printed wiring board.

6. A printed wiring board comprising the insulating film according to claim 1 or 2 and a circuit pattern layer.

Citation Information

Patent Citations

  • Film for flexible printed wiring board

    JP2023079754A